On Bringing the Controlling Debtor to Subsidiary Liability (Clause in the Ruling of the Constitutional Court of the Russian Federation in the Case of Checking the Constitutionality of Clause 3.1 of Article 3 of the Federal Law “On Limited Liability Companies” Dated May 21, 2021 No. 20-P) - T. A. Tereshchenko (Теоретическая и прикладная юриспруденция)
The article touches upon the problem of attracting persons controlling the debtor in the light of the clause on the interpretation of paragraph 3.1 of Art. 3 of the Federal Law “On Limited Liability Companies”, which was made by the Constitutional Court of the Russian Federation in the Resolution of May 21, 2021 No. 20-P. In particular, the Constitutional Court indicated that the conclusion made in the Resolution of the Constitutional Court of the Russian Federation related to the subject matter of this case cannot in itself be considered as excluding the application of the same approach to the distribution of the burden of proof in cases where another subject acts as a creditor, rather than an individual, the obligation of the company to which arose not in connection with the implementation of entrepreneurial activities by the creditor.Illustrating the grounds for ambiguous interpretation laid down in such a phrase, the author concludes that a narrowapproach is still preferable, when the clause is interpreted in favor of only such a creditor who is “another subject, theobligation of the entity to which arose not in connection with carrying out entrepreneurial activity”.According to the author, such a conclusion is not only consistent with the idea of fairness in the distribution of theburden of proof in terms of the status of creditors, but is generally consistent with the general prohibition on takingadvantage of unfair behavior.